TEORI SYAHADAT DAN TEORI EKSISTENSI HUKUM ISLAM DALAM UPAYA LEGISLASI HUKUM ISLAM DI INDONESIA - S.H, Jumarni; M.Sos, Fajar (IAIN BONE, 2024)
This article examines the position of the Shahada theory and the theory of the existence of Islamic law and their implications in the process of Islamic law legislation in Indonesia. This article uses a qualitative-normative approach with descriptive analysis techniques, the data in the article comes from processed secondary data, in the form of a literature review from various references related to the discussion. The results of the discussion in this article are: First, the theory of the Creed is a theory that requires the implementation of Islamic law by those who have uttered two sentences of the shahada, as a logical consequence of pronouncing their creed. Second, the theory of Existence, namely the theory which states that Islamic law in Indonesia: (1) Exists (exists) as an integral part of national law, (2) Exists independently, in the sense that its strength and authority is recognized as national law and given status as law. national law, (3) exist in the sense of Islamic legal norms as a filter for national law materials, and (4) exist as material and the main source of national law. Third, the presence of the theory of the application of Islamic law in Indonesia, especially the theory of shahada and the theory of existence, provides an opportunity for Islamic law to grow and develop in Indonesia.